Meta-analysis and trial sequential analysis of ezetimibe for coronary atherosclerotic plaque compositions - Bofeng Chai; Youlu Shen; Yuhong Li; Xiaoyu Wang (Frontiers Media S.A., 2023)
Background: Lipid aggregation, inflammatory cell infiltration, fibrous cap formation, and disruption are the major causes of atherosclerotic cardiovascular disease (ASCVD) and the pathologic features of atherosclerotic plaques. Although ezetimibe's role in decreasing blood lipids is widely known, there are insufficient data to determine which part of the drug has an effect on atherosclerotic plaque compositions.Objective: The study aimed to systematically evaluate the efficacy of ezetimibe for coronary atherosclerotic plaque compositions.Methods: Two researchers independently searched the PubMed, Embase, Cochrane Library, and Web of Science databases for randomized controlled trials (RCTs) on the efficacy of ezetimibe for coronary atherosclerotic plaques from inception until 22 January 2023. The meta-analysis and trial sequential analysis (TSA) were performed using Stata 14.0 and TSA 0.9.5.10 Beta software, respectively.Results: Four RCTs were finally included this study, which comprised 349 coronary artery disease patients. Meta-analysis findings showed that, compared with the control group, intervention measures could effectively reduce the fibro-fatty plaque (FFP) volume [WMD = −2.90, 95% CI (−4.79 and −1.00), and p = 0.003 < 0.05]; there were no significant difference in the reduction of fibrous plaque (FP) volume [WMD = −4.92, 95% CI (−11.57 and 1.74), and p = 0.15 > 0.05], necrotic core (NC) volume [WMD = −2.26, 95% CI (−6.99 and 2.46), and p = 0.35 > 0.05], and change dense calcification (change DC) volume [WMD = −0.07, 95% CI (−0.34 and 0.20), and p = 0.62 > 0.05] between the treatment group and the control group. TSA findings showed more studies are still required to confirm the efficacy of ezetimibe for FP and NC in the future.Conclusion: Compared to the control group, ezetimibe significantly decreased FFP, but it had no statistically significant difference on FP, NC, or change DC. According to TSA, further research will be required to confirm the efficacy of ezetimibe for FP and NC in the future.